Students’ Perceptions of Their Speaking Practice with Foreign Interlocutors via Online Platforms - Suci Tresna Dewi Handayani (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
As online platforms become more widely accessible, English learners have greater opportunities to practice speaking with foreign interlocutors, though many remain hesitant due to a lack of confidence in their speaking abilities. This study examines the perceptions of 107 first-semester English learners at a private university who were assigned to use SCMC platforms like Free4Talk, InterPals, and HelloTalk to engage in English conversations with foreign interlocutors. The aim was to understand how these platforms supported speaking practice and identify any challenges faced. Data were collected through a questionnaire that included Likert-scale items and open-ended questions. The results revealed that 78% of students had positive perceptions, indicating that the platforms facilitated their English-speaking practice through real-time communication. However, they also reported technical issues, such as poor internet connectivity, and challenges with engagement, including difficulty finding consistent conversation partners. The study recommends further research into long-term language learner experiences and an exploration of platform features that could enhance English-speaking practice.